Sarkopenia: Penilaian Kekuatan Otot Lansia dengan Diabetes Mellitus Tipe 2 Berdasarkan Indikator AWGS - Ratmawati, Ratmawati; Enardi, Ori Pertami; Emilia, Emilia (Universitas Tadulako, 2025)
The progress in Asia, AWGS (2019) re-establishes that the incidence of sarcopenia can be seen based on decrease in muscle strength. The new diagnosis was